Observation on the sedimentation pattern based on the river features using sediment river study model - Rahayu, Razali (2014)
The process of settling of suspended material by the process of gravity is known as sedimentation. It was a natural process that carries the materials such as stones and sand that form layers of solid at the bottom of water flow. Particles are deposited when the velocity cannot supports the particles anymore, which removed from the flow with the help of gravity. The main objective why this study is carried out was to determine and o1éry'e if there was any effect of the Hver characteristic on the pattern of the sediments deposited. The size distribution of the sediment was also determined at every river characteristic, to prove if the river characteristic also affects the distribution of the sediments. One river model was designed with all the characteristic to be used in this study. The river model was not designed using the actual river scale because the study was only based on the river features. The experiment was run in a few sets with different sediment placement. The water flow generated the sediments and form different pattern. The pattern is then observed and captured. The samples of sediment at selected location in the river model were sieved to identify the size of sediment. Observation from the captured image of the river at studied point, shown that there are different pattern of sedimentation due to different river features. This show that the river features also affect the procesof sedimentation. Sediment size distribution and flow strength are the factors that effect on sediment transport rates in the rivers. From the sieve analysis, it can be observed that the size of the sediment is different at different point of the river.